2014
DOI: 10.1002/jccs.201400173
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4,5‐Dihydrofuran‐3‐carbonitrile Derivatives with Electron‐Rich Alkenes in the Presence of Manganese(III) Acetate

Abstract: Radical cyclization reactions mediated by manganese(III) acetate were carried out with p-excessive alkenes (2a-d) and 3-oxopropanenitriles (1a-f) resulting in the formation of 3-cyano-4,5-dihydrofuran derivatives in poor to high yields. A mechanism was proposed for the cyclization reaction. The significance of the study is the formation of the 3-cyano-4,5-dihydrofuran derivatives resembling terfuran, 2-(2-thienyl)furan and 2-(2-benzofuryl)furyl compounds having the fluorescent properties due to a conjugated p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Similarly, aldehydes, ketones, monocarboxylic acids and their anhydrides, β-dicarbonyl compounds (such as β-diketones), β-keto esters, β-keto carboxylic acids and amides, malonic acid and its derivatives, and β-nitro carbonyl compounds are oxidized by manganese(III) acetate to attain a variety of products [15]. Manganese(III) mediation in reactions not only provides oxidative cyclization [16][17][18][19][20][21][22][23][24][25][26][27][28][29], but also enables highly diversified acetoxidation [30][31][32][33][34], halogenation [35,36], aromatization [37][38][39], oxidation [40,41], phosphonation [42,43], epoxidation [44], and also polymerization [45]. Cyclization occurs via two different mechanisms: intermolecular and intramolecular.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, aldehydes, ketones, monocarboxylic acids and their anhydrides, β-dicarbonyl compounds (such as β-diketones), β-keto esters, β-keto carboxylic acids and amides, malonic acid and its derivatives, and β-nitro carbonyl compounds are oxidized by manganese(III) acetate to attain a variety of products [15]. Manganese(III) mediation in reactions not only provides oxidative cyclization [16][17][18][19][20][21][22][23][24][25][26][27][28][29], but also enables highly diversified acetoxidation [30][31][32][33][34], halogenation [35,36], aromatization [37][38][39], oxidation [40,41], phosphonation [42,43], epoxidation [44], and also polymerization [45]. Cyclization occurs via two different mechanisms: intermolecular and intramolecular.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydrofurans are an important scaffold that occupies a prominent place in the organic syntheses, as they are present in biologically active synthetic molecules and in a wide variety of naturally occurring compounds [1,2]. Their syntheses by the radical cyclization reaction of active methylene compounds with unsaturated systems via transmetal salts (Mn 3+ , Ce 4+ , Cu 2+ ) is one of the best method [3][4][5][6][7][8][9][10][11][12][13][14]. Our research group was interested in preparing of dihydrofurans by manganese(III) acetate have shown antifungal and antibacterial activity [15,16] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has focused on the radical reaction of 1,3-dicarbonyls and 3-oxopropanenitriles with unsaturated systems. [18][19][20][21][22][23][24][25][26][27] We first reported the reaction of (E)-2-styrylthiophene and (E)-2-methyl-5-styrylfuran with 3-oxopropanenitriles, 18,20 fluorinated-1,3-dicarbonyls 21 and 1,3-diketones 22,23 lead to formation of 2-thienyl and 2-furylsubstituted trans-dihydrofurans (1 and 2). Although there are two possible different cyclization routes with these reactions, we reported that, this cyclization occurs only at the C-1 carbon (adjacent to thienyl or furyl groups) regioselectively ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%